Conditions for improved accuracy of noninvasive preimplantation genetic testing for aneuploidy: Focusing on the zona pellucida and early blastocysts - Hiroki Takeuchi; Midori Morishita; Midori Uemura; Tadashi Maezawa; Takashi Shibahara; Erina Takayama; Mikiko Nishioka; Eiji Kondo; Hiroyuki Minoura; Tomoaki Ikeda (Reproductive Medicine and Biology)
Abstract Purpose Recently, noninvasive preimplantation genetic testing for aneuploidy (niPGT‐A) using cell‐free deoxyribonucleic acid has been developed; however, there are few reports on this and the results are inconsistent. This study was conducted to optimize the cultural environment. Methods We used 35 blastocysts that had been discarded after in‐vitro fertilization. The concordance rate of karyotype analysis results between whole embryos (WEs), spent culture mediums (SCMs), and trophectoderms after 8, 16, and 24 h of culture was examined. Next, zona pellucida (ZP)‐free blastocysts and then early blastocysts were cultured for 24 h each. Results Regarding the optimal culture times, the concordance rate between WEs and SCMs was 20%, 60%, and 100% at 8, 16, and 24 h, respectively. Significant differences were found between 8 and 24 h. The concordance rate with ZP cultures was 40.0%, and no significant differences were found. The concordance rate of early blastocysts thawed and cultured for 24 h was 40.0%, which was significantly lower than that of day 5 blastocysts. Conclusions The optimal culture times for niPGT‐A were 24 h, and the concordance rate with free ZP was higher. The concordance rate for early blastocysts was low, suggesting that optimization of the conditions may be necessary.